Fine tuning the optoelectronic properties of Dibenzo[b, d]Furan-Centered linear hole transporting materials for perovskite solar cells. (July 2023) - Zahid, Waqar Ali; Akram, Waqas; Ahmad, Muhammad Fiaz; Elmushyakh, Abraham; Hossain, Ismail; Ali, S. Eltahir; Abo-Dief, Hala M.; Alanazi, Abdullah K.; Iqbal, Javed
Abstract: Perovskite solar cells (PSCs) have received a lot of interest recently due to their high efficiency, affordable manufacture, and band gap turn capacity. Reports on PSCs efficiency rose dramatically from its initial value of 3.8% in 2009 to 24% in 2022. The absence of suitable materials for hole transportation is a significant barrier to further improving efficiency. To be used as potential components of photovoltaic systems, we have designed a series of small molecules serving as hole transport materials (HTMs) namely MT1, MT2, MT3, MT4, MT5, and MT6 having dibenzo furan based donor core with end capped acceptor moieties linked by thiophene as a bridge. The photovoltaic and optoelectronic properties of the molecules have been investigated by comparing them to a reference molecule (R ). All of the designed molecules (MT1 -MT6 ) showed lower bandgaps (1.98 eV–2.61 eV) than reference molecule (3.81 eV), indicating improved electron density transfer. All designed molecules (MT1 -MT6 ) have high open-circuit voltage (1.28 V–1.41 V) and downshifted peak occupied molecular orbital energies (−5.41 eV to −5.28 eV) when electron-withdrawing acceptor moieties are chosen. High dipole moments (5.18 D to 21.70 D) proved that designed molecules (MT1 -MT6 ) are highly soluble and are anticipated to make it easier to fabricate multilayered films. All designed molecules have effective charge transport capabilities, as evidenced by the reorganization energy values. All HTMs (MT1 -MT6 ) have higher FF (0.9032–0.9102) and superior power conversion efficiency of 27.40% –30.42% compared to R (24.62% ). This study established the viability of fabricating high performance PSCs using all proposed molecules (MT1 -MT6 ). Graphical abstract: Image 1 Highlights: The end-capped acceptors engineering of dibenzo[b, d]furan-centered linear HTM endowed with six newly designed molecules (MT1-MT6 ). Deeper HOMO energy levels manifest high VOC. The molecules absorb in UV–visible and near IR region manifested with low bandgaps, excitation, and binding energy. The molecules exhibit superior hole mobilities than that of the benchmark Spiro-OMeTAD.